Solubility of carbon monoxide and hydrogen in propylene carbonate and thermomorphic multicomponent hydroformylation solvent - Shaharun, Maizatul Shima; Mukhtar, Hilmi; Dutta, Binay Kanti (Elsevier, 2008)
Solubilities of carbon monoxide and hydrogen in propylene carbonate (PC), biphasic mixture of PC and dodecane (1:1 v/v) and thermomorphic (or temperature dependent) multicomponent solvent (TMS)-system consisting of PC, dodecane and 1,4-dioxane were measured over the temperature and pressure range of 298–343K and 0.1–1.5MPa, respectively, in a high pressure solubility cell. The measured solubilities were correlated by a temperature-dependent Henry’s law constant and interpreted by activity coefficient models based on the regular solution theory (RST) with Yen and McKetta extension for polar solvents as well as by the UNIFAC group contribution method. The experimental data showed a very good fit in terms of Henry’s law constant except for H2–PC and CO–PC binaries. The RST-based model, that did not involve any adjustable constant, could predict the experimental solubility to within ±11.0% error. The UNIFAC model worked better with the interaction parameters computed as a linear function of temperature using a part of the experimental solubility data set. The accuracy of prediction was found to be within a maximum error of ±8.5%. The TMS system shows higher affinity for CO and H2, which is comparable to the single phase PC. The experimental solubilities in the liquids are substantially larger than those in most other hydroformylation solvents thereby establishing its advantage over the alternative solvents for industrial use. Liquid–liquid equilibrium for the TMS system consisting of PC, dodecene and 1,4-dioxane system was also measured at 298, 353 and 373 K.